Social cognition in schizophrenia. [article]. - Penn, D. L.
The study of social cognition in schizophrenia may augment the understanding of clinical and behavioral manifestations of the disorder. In this article, the authors describe social cognition and differentiate if from nonsocial cognition. They garner evidence to support the role of social cognition in schizophrenia: Nonsocial information-processing models are limited to explain social dysfunction in schizophrenia, measures of social, cognition may contribute greater variance to social functioning than measures of nonsocial cognition, task performance on nonsocial-cognitive measures may not parallel performance on social-cognitive tasks, and symptomatology may be best understood within a social-cognitive framework. They describe the potential implications of the social-cognitive model of schizophrenia for the etiology and development of the disorder. -- (from the author)